Green Melodies at Work: A Phenomenological Study of Environmental Awareness and Green HRM Practices - M. Ikhwan Maulana Haeruddin (Abadi Institute, 2026)
Environmental sustainability has become a strategic priority for organizations, increasing the importance of Green Human Resource Management (GHRM) as a mechanism for fostering environmentally responsible employees. Although previous studies have demonstrated positive relationships between GHRM and environmental performance, limited research has explored how employees subjectively experience GHRM practices and how these experiences shape environmental awareness, particularly in the Indonesian context. This study aims to explore employees’ lived experiences of GHRM practices and their influence on environmental awareness within Indonesian organizations. A qualitative phenomenological approach was employed, involving semi-structured interviews with twelve employees from the manufacturing, hospitality, and service sectors. Data were analyzed using Braun and Clarke’s reflexive thematic analysis. The findings revealed four interconnected themes: Environmental Awareness, Green Work Behavior, Organizational Support, and Sustainability Culture. Employees generally demonstrated strong environmental concern; however, many lacked a clear understanding of how organizational sustainability initiatives related to their specific job responsibilities. Leadership commitment, environmental infrastructure, and culturally embedded values emerged as key factors influencing environmental engagement. The study concludes that effective GHRM implementation requires more than formal environmental policies; it necessitates integrated systems that enhance employee capabilities, create participation opportunities, and align sustainability initiatives with employees’ cultural and ethical values. These findings contribute to the growing GHRM literature by providing a deeper understanding of the mechanisms through which environmental awareness is cultivated in developing-country workplaces.